Role of innovations and impact on economic development in MENA countries - Boadu, Martin Amofa (Univerzita Pardubice, 2024)
Economic growth in MENA countries is advancing due to innovative measures despite the prevailing instability. Developing new opportunities through the diversification of industries and innovation is crucial. The research will assess the factors that drive innovation in the MENA region and propose ways to enhance them. The objective is to scrutinize the impact of innovation on economic development in countries within MENA by studying their innovation milieu and providing suggestions based on outcome evaluation.
Keywords: ekonomický rozvoj; inovace a země MENA; economic development; innovation and MENA countries